MNK2-eIF4E axis promotes cardiac repair in the infarcted mouse heart by activating cyclin D1. (May 2022) - Chen, Bing-Rui; Wei, Tian-Wen; Tang, Chun-Ping; Sun, Jia-Teng; Shan, Tian-Kai; Fan, Yi; Yang, Tong-Tong; Li, Ya-Fei; Ma, Yao; Wang, Si-Bo; Wang, Zi-Mu; Wang, Hao; et al.
Abstract: Adult mammals have limited potential for cardiac regeneration after injury. In contrast, neonatal mouse heart, up to 7 days post birth, can completely regenerate after injury. Therefore, identifying the key factors promoting the proliferation of endogenous cardiomyocytes (CMs) is a critical step in the development of cardiac regeneration therapies. In our previous study, we predicted that mitogen-activated protein kinase (MAPK) interacting serine/threonine-protein kinase 2 (MNK2) has the potential of promoting regeneration by using phosphoproteomics and iGPS algorithm. Here, we aimed to clarify the role of MNK2 in cardiac regeneration and explore the underlying mechanism. In vitro, MNK2 overexpression promoted, and MNK2 knockdown suppressed cardiomyocyte proliferation. In vivo, inhibition of MNK2 in CMs impaired myocardial regeneration in neonatal mice. In adult myocardial infarcted mice, MNK2 overexpression in CMs in the infarct border zone activated cardiomyocyte proliferation and improved cardiac repair. In CMs, MNK2 binded to eIF4E and regulated its phosphorylation level. Knockdown of eukaryotic translation initiation factor (eIF4E) impaired the proliferation-promoting effect of MNK2 in CMs. MNK2-eIF4E axis stimulated CMs proliferation by activating cyclin D1. Our study demonstrated that MNK2 kinase played a critical role in cardiac regeneration. Over-expression of MNK2 promoted cardiomyocyte proliferation in vitro and in vivo, at least partly, by activating the eIF4E-cyclin D1 axis. This investigation identified a novel target for heart regenerative therapy. Graphical abstract: Unlabelled Image Highlights: Neonatal mice can regenerate completely after heart injury, while adult mice lose this ability MNK2 protein kinase is first found to promote cardiomyocyte proliferation and cardiac regeneration MNK2 do not affect heart growth of healthy mouse MNK2-eIF4E-cyclin D1 axis is first proved to promoted cardiomyocyte proliferation